Penggunaan Polivinil Pirolidon (PVP) sebagai Bahan Pengikat pada Formula Granul: Literatur Review - Safitri, Rusiana Yulia; Bhagawan, Weka Sidha; Primiani, Cicilia Novi Primiani (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2024)
Granule preparations are lumps of small particles that are uneven in shape and become single, larger particles. The process of making granule preparations uses a technique, namely granulation. In the granulation process, a binder is needed to unite the powder particles into a granule preparation. The binder material that is often used is polyvinyl pyrrolidone (PVP). The use of PVP is able to produce an optimal granule preparation that meets the requirements. This research reviews the use of PVP as a binding agent in making granule preparations. This research method uses a literature study method in the form of primary references in the form of national journals from the last 10 years searched in the Google Scholar, PubMed, and ScienceDirect databases. Search for this data source using the keywords Use of PVP as a binding agent in granule preparations. The results and conclusions of the research show that the use of PVP as a binding agent in granular preparations can produce preparations that meet the requirements.